1972
DOI: 10.1007/bf00583410
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of mutagenic effectiveness and efficiency of NMU and MNG in Sorghum

Abstract: A comparative study of the effectiveness and efficiency of NMU and MNG in relation to the effects in M1 plants and induction of mutations in M2 was made in a cultivated variety ofSorghum. There was a decrease in the values obtained in each of the biological criteria in the M1, namely germination, survival, seedling growth and seed fertility, with an increase in the concentration of NMU and MNG. Of the characters, survival following MNG treatments and seed fertility following NMU treatments showed the maximum r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…In the case of NMU, treatments of seeds with the 9 mM solution for 8 h could be proposed for enhancing the mutagen efficiency. This finding also confirms the earlier results of Ramulu (1972) with sorghum who observed that lower dosages of NMU are more efficient than higher concentrations. Mean comparisons of the effect of sodium azide treatment revealed that 8 h non-soaking seed treatment with 6 mM solution of this mutagen induced 50% reduction in germination percentage compared to that of the control treatment (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…In the case of NMU, treatments of seeds with the 9 mM solution for 8 h could be proposed for enhancing the mutagen efficiency. This finding also confirms the earlier results of Ramulu (1972) with sorghum who observed that lower dosages of NMU are more efficient than higher concentrations. Mean comparisons of the effect of sodium azide treatment revealed that 8 h non-soaking seed treatment with 6 mM solution of this mutagen induced 50% reduction in germination percentage compared to that of the control treatment (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…Reduction in germination in mutagenic treatments has been explained due to delay or inhibition of physiological and biological processes necessary for seed germination, which include enzyme activity (Kurobane et al 1979 ), hormonal imbalances (Chrispeels and Varner 1967 ), and inhibition of mitotic processes (Ananthaswamy et al 1971 ). The greater sensitivity at higher doses of mutagens has been attributed to various factors, such as changes in the metabolic activity of the cells (Natarajan and Shiva Shankar 1965 ), inhibitory effects of the mutagen (Sree Ramulu 1972 ), and disturbances of the balance between promoters and inhibitors of growth regulators (Meherchandani 1975 ).…”
Section: Biological Damagementioning
confidence: 99%